PENGARUH AUDIT KNOWLEDGE, AUDIT EXPERIENCE, SELF-EFFICACY TERHADAP AUDIT JUDGEMENT: PERAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERATING - Rahayu Noviranza; Aqamal Haq (EBID: Ekonomi Bisnis Digital, 2024)
This study aims to examine the effect of Audit Knowledge, Audit Experience, Self-Efficacy on Audit Judgement with Job Complexity as an Moderating Variable. This type of research is quantitative research. The data used in this study is primary data. The population in this study are all auditors at Public Accounting Firms in the City of Jakarta and the sample of this study are auditors who had worked for more than one year and had carried out audit tasks. Data was obtained from 155 respondents. The analysis used is a multiple linear regression analysis method. The results of the analysis show that Audit Knowledge, Audit Experience, Self-efficacy have a positive effect on Audit Judgement. Job complexity weakens the influence between Audit Knowledge and Self-efficacy on Audit Judgement. However, Job Complexity strengthens the influence of Audit Experience on Audit Judgement.